Management and information technology in the digital era : challenges and perspectives - Chemma, Nawal; Abdelli, Mohammed El Amine; Awasthi, Anjali, 1976-; Mogaji, Emmanuel (Emerald Publishing Limited, 2022)
Management of information technology will continue to be an essential endeavour for organisations as we experience the accelerating advancement of digital technology. Managers will need to understand how technology is changing their business operations and the emergence of digital consumers who demand more innovative, technologically driven experiences. This 29th volume in the Advanced Series in Management is built to provide theoretical insight for managers and researchers to co-create their technology values and better understand its prospects and challenges. Management and Information Technology in the Digital Era: Challenges and Perspectives explores the management and practical implications of digital information management across a broad range of technologies, sectors, and countries. Chapters from a spectrum of international authors provide a significant contribution to the growing body of work on information technology, artificial intelligence, and technology management, reflecting the diversity of current research and delving into the varying perspectives of management and information technology in the digital era. Significantly recognised are the growing prospects of Artificial intelligence and how it is revolutionising different sectors, further presenting critical challenges for managers on how to harness the prospects of this technology for their business prospects.
Keywords: Information technology -- Management.; Industrial management -- Data processing.; Business & Economics -- Management.; Management & management techniques.; elektronické knihy; electronic books